Synthesis and characterization of sulfur-functionalized silica nanocapsules as mercury adsorbents - Palaniappan, T. (American Institute of Physics Inc., 2017)
Sulfur functionalized silica nanocapsules (S-SiNC) was successfully synthesized and characterized as a potential adsorbent for industrial applications. The synthesis of S-SiNC was carried out using the mircoemulsion templating method using cetyltrimethylammonium bromide (CTAB) as cationic surfactant, toluene as co-solvent, ammonia solution as catalyst, and tetraethylorthosilicate (TEOS) as the silica base. The S-SiNC adsorbent was characterized using Transmission Electron Microscope, Fourier Transformed Infra Red spectroscopy and nitrogen adsorption/desorption analysis. The physical and chemical properties of the SiNC changed as a result of the functionalization, hence affecting the extent of Hg(II) adsorption. The S-SiNCs were also tested in mercury ion Hg(II) adsorption via batch adsorption process with variation in initial Hg (II) concentration. It was found that there is a significant improvement in Hg(II) adsorption performance after being functionalized with elemental sulfur. The highest Hg(II) adsorption capacity was obtained for S-SiNC (107.875 mg/g), which significantly outperformed the blank SiNC. The experimental data obtained was found to be fitting well to the Langmuir isotherm model (R2= 0.979) compared to Freundlich isotherm model. Thus, the results demonstrated the potential application of sulfur functionalized silica nanocapsules as adsorbent in industrial applications. © 2017 Author(s).